Group membership and adolescents’ third-party punishment: a moderated chain mediation model - Zhang, Zhen; Li, Menghui; Liu, Qiyun; Chen, Chao; Qi, Chunhui (Frontiers in Psychology, 2023)
Third-party punishment (TPP) reflects people’s social preference for fairness norms and is fundamental to maintaining fairness norms on a large scale. Several empirical studies have shown that the offender’s group membership impacts TPP, but the detailed mechanisms have yet to be fully elucidated. The current study used the third-party punishment game task to explore the relationship between group membership, perceived unfairness, anger, and adolescents’ TPP. A total of 306 teenagers aged 12 to 15 were chosen as subjects through cluster sampling. The results showed that group membership (classmate vs. stranger) and gender can affect adolescents’ TPP together, which manifests as adolescents enacting significantly harsher punishments on strangers than on classmates, especially for boys. Group membership indirectly affects TPP through the mediating effects of perceived unfairness, anger and through a chain mediation of perceived unfairness and anger. Moreover, gender positively moderate the relationship between group membership and perceived unfairness. Specifically, group membership significantly affects boys’ perceived unfairness, but cannot predict girls’ perceived unfairness. The above results can be used to guide adolescents toward appropriate justice concepts and moral awareness, thus enhancing TPP.